The endosperm-specific transcription factor TaNAC019 regulates glutenin and starch accumulation and its elite allele improves wheat grain quality. Issue 3 (2nd January 2021) - Gao, Yujiao; An, Kexin; Guo, Weiwei; Chen, Yongming; Zhang, Ruijie; Zhang, Xue; Chang, Siyuan; Rossi, Vincenzo; Jin, Fangming; Cao, Xinyou; Xin, Mingming; Peng, Huiru; et al.
Abstract: In wheat ( Triticum aestivum L.), breeding efforts have focused intensively on improving grain yield and quality. For quality, the content and composition of seed storage proteins (SSPs) determine the elasticity of wheat dough and flour processing quality. Moreover, starch levels in seeds are associated with yield. However, little is known about the mechanisms that coordinate SSP and starch accumulation in wheat. In this study, we explored the role of the endosperm-specific NAC transcription factor TaNAC019 in coordinating SSP and starch accumulation. TaNAC019 binds to the promoters of TaGlu-1 loci, encoding high molecular weight glutenin (HMW-GS), and of starch metabolism genes. Triple knock-out mutants of all three TaNAC019 homoeologs exhibited reduced transcript levels for all SSP types and genes involved in starch metabolism, leading to lower gluten and starch contents, and in flour processing quality parameters. TaNAC019 directly activated the expression of HMW-GS genes by binding to a specific motif in their promoters and interacting with the TaGlu-1 regulator TaGAMyb. TaNAC019 also indirectly regulated the expression of TaSPA, an ortholog of maize Opaque2 that activates SSP accumulation. Therefore, TaNAC019 regulation of starch- and SSP-related genes has key roles in wheat grain quality. Finally, we identified an elite allele ( TaNAC019-BI ) associated with flour processing quality, providing a candidate gene for breeding wheat with improved quality. Abstract : The wheat seed-specific transcription factor TaNAC019 regulates storage protein and starch accumulation by cooperating with TaGAMyb, and the TaNAC019-BI allele is candidate for higher processing quality in breeding.